The Health Services White Paper : The Labour Party's policy
1944-09 1944 1940s 22 pages - 5 - (e) Ill-health is a universal risk. Everyone is entitled to the best possible treatment. The Labour Party therefore gives its full support to the principle of universality. The White Paper, however, goes on to propose that all doctors - with a few exceptions - shall have the right to treat patients privately for fees. Thus every patient will be able to see his doctor or specialist either privately or as a public patient. The White Paper states that there must be no discrimination; but if there is no discrimination, why should anyone pay fees? This is a dangerous compromise which may lead to two standards of treatment in the new service. There is, however, one answer to it. If everyone, or almost everyone, elects to exercise their rights and receive treatment through the public service, there can only be one standard. With this hope in mind, the Labour Party is reluctantly prepared to accept this compromise. Doctors, and in particular, general practitioners, dislike local authorities, and local authority work. This is partly because, in the past, local authorities have undertaken work which G.P.s think should have been left to them, and partly because the medical services run by some local authorities have been bad. There are notable exceptions, but the doctors' prejudices have had some foundations. For this reason, many doctors have suggested a corporation or board appointed by the Government, to run a national health service. As far as the general practitioners are concerned, the Government has accepted this proposal. The White Paper suggests a Central Medical Board. The Board will be a small body, appointed by the Minister, mainly professional but with some lay members. All general practitioners in the public service will make contracts with the Board, and will be paid by it. There will be local Board committees in each area, on which local authority members will be included. The doctors are now attacking the idea of a Central Medical Board on two grounds. First, it is suggested that its medical members should not be appointed by the Minister but should be elected by the profession. This fantastic proposal would permit the profession to pay itself the public's money; it cannot for one moment be contemplated. Secondly, it is said that all doctors - hospital doctors, consultants and specialists, as well as G.P.s - should be employed by the Board and not by the hospital authorities. This is a less unreasonable proposal, since it would at least have the merit of unifying the service as far as the doctors are concerned. But it would separate the doctors from other health workers and from the hospitals in which they work. The Labour Party considers that the only sound solution is for the general practitioners and specialists to be employed by the new joint authorities which will control the hospitals. This would provide for a unified general practitioner and specialist and hospital service; it would preserve democratic control; and it would enable area planning to be far more effective than it would be under the White Paper scheme. 292/847/3/166